Cable-like double-carbon layers for fast ion and electron transport: An example of CNT@NCT@MnO2 3D nanostructure for high-performance supercapacitors. (March 2019) - Wang, Yinghui; Zhang, Deyang; Lu, Yang; Wang, Weixiao; Peng, Tao; Zhang, Yingge; Guo, Yan; Wang, Yange; Huo, Kaifu; Kim, Jang-Kyo; Luo, Yongsong
Abstract: A unique nanostructure consisting of CNTs as carbon matrix, and were sequentially coated with silicon dioxide, N-doped porous carbon tube (NCT) and MnO2 nanoflowers, the final CNT@NCT@MnO2 composites with large internal voids between CNT and NCT. CNT@NCT@MnO2 combines the nanostructural advantages of internal voids and the N-doped porous carbon, presenting fast diffusion paths for ions and electrons, high conductivity and large surface areas. When used as an anode material in supercapacitors, the CNT@NCT@MnO2 tube-in-tube hierarchical nanostructure exhibite a remarkably excellent electrochemical behavior with a specific capacitance (Csp) of 210 F g −1 at the current density of 0.5 A g −1 . Moreover, all-solid-state asymmetrical supercapacitors (ASCs) were fabricated using the CNT@NCT@MnO2 composites as anode and the CNT@NCT as cathode, Na2 SO4 /PVA gel as the electrolyte and the separator. The all-solid-state ASCs also show the superior performance, such as high energy density of ∼14 Wh kg −1 and a power density of ∼3.6 kW kg −1 . Graphical abstract: The 3D CNT@NCT@MnO2 composites have been synthesized by sacrificial template method. These kind of unique tube-in-tube nanostructures connected together make a 3D traffic network, which is important for the diffusion of electrolyte ions and the internal voids between CNT and NCT provide additional electroactive sites. When used as an anode material in supercapacitors, the CNT@NCT@MnO2 tube-in-tube hierarchical nanostructure exhibite a remarkably excellent electrochemical behavior.